Cântecul lui Ioasaf şi verşul Sfântului Alexie, omul lui Dumnezeu. O abordare literară - Cristina-Ioana Dima (Revista de Istorie și Teorie Literară)
The Anthem of Josaphat and the Stance of Saint Alexis are, in fact, the same poem about the eremitic life. The first part of our study analyses the confusion of these two characters to whom is dedicated the poem. From the hagiographic works we find out that the Prince Josaphat finished his life in the Indian desert and the nobelman Alexis passed his last years incognito in his father’s yards. There are two different ways to fulfill the same aim of an eremitic life. This constatation allows us to suggest in the second part of our paper that the real message of our text is the glorification of any kind of the sacred space which terrifies and offers, in the same time, the opportunity of meeting the divinity. Hereby, the poem is included in the hymnographic genre.